THE IMPACT OF ARTIFICIAL INTELLIGENCE ON BANKING OPERATIONS - Neharika; Yadav, Sanjay Kumar; Kadakia, Babita (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research explores the impact of artificial intelligence on India’s private banking industry, with particular emphasis placed on how AI transforms banking processes and client engagement. A descriptive research approach was adopted in collecting opinions from private bank customers and staff. In total, all 50 staff and 150 clients participated in the survey and provided information through standardized questionnaires. The research has examined quite a few AI applications, like chatbots in customer care, software for fraud detection, AI-based banking services, and investment product recommendation. Customers are largely found to be satisfied with AI applications, as per the research, but there still exist big issues with trust and security issues; those issues are especially significant when it is a matter of fraud detection and investment suggestions. According to the employees, artificial intelligence helps in enhancing customer satisfaction, risk management, and operational efficiency. However, they also add that employees need additional training to gain full understanding of the AI system. In the study, the importance of human involvement in decision-making, trust, and security matters is highlighted while also outlining potential advantages of AI in optimizing banking operations. The report gives an in-depth insight into how AI is affecting employee processes and client experiences in India’s private banking industry through regression and correlation analysis.